Phagocytic Activity of Neutrophils in the Blood of Pigs that Received A “Microecological System” Alternative to Antibiotics - V. Krapivina, Elena; A. Menkova, Anna; V. Ivanov, Dmitry; A. Kasheev, Alexander; L. Talyzina, Tatiana (International Journal of Psychosocial Rehabilitation, 2020)
The study was aimed at the identification of a certain link of the nonspecific protection in pigs that enhances its activity during the application of different feeding plans with the probiotic "EM-Vita," creates a stable “microecological system," and provides high natural resistance. Weaned piglets aged 46-53 days were distributed into 3 groups by the method of analog pairs: Group I—the control group; Group 2—and Group 3—the test groups that received even doses of the drug but at different intervals. It was established that in 2 months, pigs that received “EM-Vita” by both schemes had expressed an increase in the level of nonspecific protection due to a general increase in the neutrophil count and their fractions capable of both oxygen-dependent microbicide activity and enhanced activity of this process. The application of the drug by one of the schemes provided the creation of the adaptive reserve of neutrophils that exert adsorptive activity by the other scheme—the increase in the synthesis of cationic proteins. Thus, the periodicity of the application of the probiotic “EM-Vita” significantly influences the status of neutrophils by selective activation of different protective systems.